Possession in Football: More Than a Quantitative Aspect – A Mixed Method Study - Casal, Claudio A.; Anguera, M. Teresa; Maneiro, Rubén; Losada, José L. (Frontiers in Psychology, 2019)
The aim of the present study was to identify and differentiate the factors that determine the possession times of successful and unsuccessful elite football teams, with the purpose of determining an effective possession model. For this, match corresponding to the round of eighth-finals, quarterfinals, semifinals and final of the 2016 UEFA Euro France in which 2,636 offensive sequences occurred, were analyzed. Video recordings of matches were analyzed and coded post-event using notational analysis. The performance indicators recorded and analyzed were: phase; match period; type of start-up; interaction context; intention; field zone; possession time, passes, attack outcome; match status and final outcome. An ANOVA was performed to analyze data in order to study the influence of a set of variables. A BoxCox transformation was applied on the variable explained to achieve normal conditions. A study of the main effects and significant interactions was also carried out, complemented with a set of predictions with the variables that were more significant. Results show how, in successful teams, possession time is influenced by: Type of start-up, intention and field zone. On the other hand, in unsuccessful teams, possession time is determined fundamentally by intention and match status. In terms of the results of the predictive models, in the case of successful teams, they will have longer possessions in the offensive zone with the score in favor and, in the defensive zone with a draw score, in both situations, initiating them by means of a transition. For unsuccessful teams, possessions will be of longer duration in the defensive zone with a draw score, regardless of the type of start-up and, in the offensive zone, losing and initiating the play by means of a set ball action and winning by means of a transition. Results obtained in this work identify key factors that determine possession time in teams and allow to differentiate the possessions of successful and unsuccessful teams, identifying a more effective ball possession model. This information can be used to design a possession model with greater probabilities of success and increase the offensive performance of teams.